2011
DOI: 10.1002/marc.201100482
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Rolled Polymer Tubes: Novel Tools for Microfluidics, Microbiology, and Drug‐Delivery Systems

Abstract: Recent work on the fabrication of tubular microstructures via self-rolling of thin, bilayer polymer films is reviewed. A bending moment in the films arises due to the swelling of one component of the bilayer in a selective solvent. The inner diameters of the tubes vary from hundreds of nanometers to dozens of micrometers. The position of the tubes on the substrate and their length can be preset by photolithographic patterning of the bilayer. Prior to rolling, the bilayers can be exposed to different methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Rolling, in this system, is achieved due to the swelling of the P4VP in a water solution of an acid, due to protonation of the pyridine rings [80]. In another study of Ionov, self-rolling due to swelling was observed.…”
Section: Self-folding Polymersmentioning
confidence: 77%
“…Rolling, in this system, is achieved due to the swelling of the P4VP in a water solution of an acid, due to protonation of the pyridine rings [80]. In another study of Ionov, self-rolling due to swelling was observed.…”
Section: Self-folding Polymersmentioning
confidence: 77%
“…Mechanical stress arises from structural heterogeneities in the film, 2 such as chemical inhomogeneities due to a gradient in composition, [3][4][5] differences in the lattice constants between the top and bottom layers, 6,7 or differences in the degree of crosslinking in the case of polymers. Detachment of the film with release of the strain causes scrolling of the layer and the formation of tubes and rolls; this mechanical response is quite general and has been observed in various materials such as metals, 8 semiconductors, 9,10 polymers 11,12 and oxides. 13 The main strategy that has been employed thus far is to induce the stress by fabricating bilayer or multilayer films, in which the mismatch between the two layers is used as the bending driving force.…”
Section: Introductionmentioning
confidence: 96%
“…However, proposed strategies generally apply only to specific polymer combinations [3] or include HF release strategies [4]. The latter is especially not appropriate as traces of HF may remain inside the hydrogel network, diffuse out over time only, and eventually compromise bio-compatibility.…”
Section: Introductionmentioning
confidence: 99%